Food price spikes: Is a cereal export ban the right response for Ethiopia? - Aragie, Emerta A.; Balié, Jean; Morales-Opazo, Cristian (John Wiley & Sons, 2020)
Following the price hikes of 2007–2008 and 2010–2011, many governments in low-income countries implemented food export bans. While several studies investigate the macroeconomic impacts of such bans on large net exporters of grains, only very few country case studies have examined the economy-wide and distributional effects combined. Further, there is a lack of rigorous studies that explicitly analyse cereal export bans as policy responses to external price shocks and their net combined effects, both in the immediate and in the short run. This article evaluates this situation for the case of Ethiopia, a net food-importing country. We find that international price shocks not only do affect domestic prices but could also considerably suppress domestic food production and supplies. A cereal export ban can help stabilize domestic food prices but cannot fully erase the price hike. We, however, note that the ban further discourages domestic cereal production and reduces rural households’ welfare.